Dual targeting of folate receptor-expressing glioma tumor-associated macrophages and epithelial cells in the brain using a carbon nanosphere–cationic folate nanoconjugate. Issue 9 (30th July 2019) - Elechalawar, Chandra Kumar; Bhattacharya, Dwaipayan; Ahmed, Mohammed Tanveer; Gora, Halley; Sridharan, Kathyayani; Chaturbedy, Piyush; Sinha, Sarmistha Halder; Chandra Sekhar Jaggarapu, Madhan Mohan; Narayan, Kumar Pranav; Chakravarty, Sumana; Eswaramoorthy, Muthusamy; Kundu, Tapas Kumar; et al.
Abstract : A carbon nanosphere-based dual strategy to target tumor-associated macrophages and tumor cells in glioma lesions within the brain. Abstract : Glioblastoma multiforme (GBM), the highly invasive form of glioma, exhibits the highest mortality in patients with brain malignancies. Increasing glioma patients' survivability is challenging, as targeting only tumor-associated malignant cells would not reduce the overall aggressiveness of the tumor mass. This is due to the inadequacy in countering pro-proliferative, invasive and metastatic factors released by tumor-mass associated macrophages (TAMs). Hence, strategically, dual targeting both tumor cells and TAMs is necessary for effective glioma treatment and increased survivability. Conventional FR-targeting systems can easily target cancer cells that overtly express folate receptors (FRs). However, FRs are expressed only moderately in both glioma cells and in TAMs. Hence, it is more challenging to coordinate dual targeting of glioma cells and TAMs with lower levels of FR expression. A recently developed carbon nanosphere (CSP) with effective blood–brain barrier (BBB) penetrability was modified with a new folic acid–cationic lipid conjugate (F8) as a targeting ligand. The uniqueness of the cationic lipid–folate conjugate is that it stably associates with the negatively charged CSP surface at about >22 mol% surface concentration, a concentration at least 5-fold higher than what is achieved for conventional FR-targeting delivery systems. This enabled dual uptake of the CSP on TAMs and tumor cells via FRs. A doxorubicin-associated FR-targeting formulation (CFD), in an orthotopic glioma model and in a glioma subcutaneous model, induced the maximum anticancer effect with enhanced average mice survivability twice that of untreated mice and without any systemic liver toxicity. Additionally, we observed a significant decrease of TAM-released pro-aggressive factors, TGF-β, STAT3, invasion and migration related sICAM-1, and other cytokines indicating anti-TAM activity of the CFD. Taken together, we principally devised, to the best of our knowledge, the first FR-targeting nano-delivery system for targeting brain-associated TAMs and tumor cells as an efficient glioma therapeutic.